Hubble space telescope observations of the gravitationally lensed cloverleaf broad absorption line QSO H1413+1143: imaging - ESPEY, BRIAN RUSSELL (American Astronomical Society, 1996)
An analysis of Hubble Space Telescope (HST) Wide Field Planetary Camera (WFPC) and Wide Field Planetary Camera 2 (WFPC2) images of the gravitationally lensed Cloverleaf broad absorption line quasi-stellar object (QSO) H1413+1143 is presented. Astrometric and photometric measurements are derived for the four components of the lensed QSO for five different epochs over a baseline of 2.76 yr. Because of the replacement of WFPC with WFPC2 and the change in the purpose of the observation at the various epochs, the data were not always taken with the same filter. With the exception of the declination of component D, the relative positions of the four components are measured to within ~3 mas; these results are consistent with but considerably more accurate than earlier measurements. The relative photometric measurements at any one epoch are typically accurate to ~0.02--0.03 mag (1 sigma ). The initial HST WFPC images cover a baseline of 1.26 yr (1992.21--1993.47 [1992 March 16--1993 June 22]), and over this time interval there is little evidence for brightness variations of any of the components relative to one another at levels >0.06 mag (>2 sigma ). Photometric measurements of the more accurate WFPC2 data obtained with different filters extends this baseline an additional 1.50 yr (to 1994.97 [1994 December 22]). The WFPC2 data also fail to reveal significant brightness variations among the components. In addition, the WFPC2 data include both UV (F336W) and near-infrared (F814W) images. These color data indicate the presence of sight-line--dependent extinction, causing the F336W--F814W color index of component B (the most reddened component) to be 0.56 +/- 0.04 mag redder than that of component C (the least reddened component). The lack of evidence for significant component brightness variations at all HST observation epochs suggests that the data could be reliably extinction-corrected to derive the relative amplifications of the four image components. This is done for several reasonable dust-extinction models. Thus, the derived astrometry along with the photometric analysis set clear constraints on models for the Cloverleaf. Since component D shows some evidence for microlensing, the results on its relative amplification should be used with caution. While existing models can successfully reproduce the relative positions, the relative amplifications have not yet been successfully modeled. The WFPC2 imaging data has also permitted a sensitive search for component structure and the gravitational lens itself. There is marginal evidence for elongated structure between components A and C that may be part of an Einstein ring. However, no significant evidence for the lensing object is found. The various measurements are quantified in ways useful for setting model constraints. Limits on the mass-to-light ratio and detectability of the lensing galaxy are also discussed.
PUBLISHED
Keywords: Physics